Corruption and the efficiency of capital investment in developing countries - Conor M. O'Toole; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
This paper considers the effect of corruption on the effciency of capital investment. Using firm-level level data from the World Bank enterprise surveys, covering 90 developing and transition economies, we consider whether the cost of informal bribe payments distorts the efficient allocation of capital by reducing the marginal return per unit investment. Using country estimates of fractionalization and legal origin as instruments, and controlling for censoring, we find that bribery decreases investment efficiency, as measured using both absolute and relative metrics of investment returns. The negative effect is strongest for domestic small and medium-sized enterprises while there is no significant effect on foreign and large domestic firms. We conclude that reducing the level and incidence of bribery by public officials would facilitate a more efficient allocation of capital. This in turn would support economic growth and development, particularly for small and medium-sized enterprises.
Keywords: D72; D73; D92; E22; G31; 330; corruption; efficiency; rent-seeking; capital investment; Kapitalanlage; Korruption; Rent-Seeking